Crisis, Response and Distributional Impact: The Case of Ireland - CALLAN, TIM; NOLAN, BRIAN; KEANE, CLAIRE; SAVAGE, MICHAEL; WALSH, JOHN R. (ESRI)
Ireland is one of the countries most severely affected by the Great Recession. National income fell by more than 10 per cent between 2007 and 2012, as a result of the bursting of a remarkable property bubble, an exceptionally severe banking crisis, and deep fiscal adjustment. This paper examines the income distribution consequences of the recession, and identifies the impact of a broad range of austerity policies on the income distribution. The overall fall in income was just under 8 per cent between 2008 and 2011, but the greatest losses were strongly concentrated on the bottom and top deciles. Tax, welfare and public sector pay changes over the 2008 to 2012 period gave rise to lower than average losses for the bottom decile. Thus, the larger than average losses observed overall are not due to these policy changes; instead, the main driving factors are the direct effects of the recession itself. Policy changes do contribute to the larger than average losses at high income levels.
PUBLISHED
Keywords: Economics